ANALISIS UPAYA TRUST BUILDING PEMERINTAH KABUPATEN KLATEN DIBAWAH KEPEMIMPINAN BUPATI SRI MULYANI - Muchlas Adi Nugroho; Laila Khalid Alfirdaus (Journal of Politic and Government Studies, 2020)
The emergence of the phenomenon of political dynasties and cases ofbribery of promotion of job titles caused public trust to the Klaten RegencyGovernment declined. The new Klaten Regent, Sri Mulyani has a big responsibilityin improving governance while at the same time restoring public trust. Regent SriMulyani on the other hand turned out to have ambitions to run again as KlatenRegent in the 2020 elections. The ambition made the trust building effortsundertaken by the Klaten Regency Government prone to political interests.The purpose of this study is to explain the trust building efforts undertakenby the Klaten Regency Government under Sri Mulyani Regent and to analyze theinfluence of Sri Mulyani Regent's political interests ahead of the 2020 elections inthe implementation of trust building efforts. The method used in this study is aqualitative explorative method of primary data in this study obtained directly frominterviews with resource persons, while secondary data is obtained indirectlythrough documents, mass media, social media, and internet. The theoretical basisused is the theory of trust, governance and bureaucratic reform.Based on data from the results of field research, the Klaten RegencyGovernment under the leadership of Sri Mulyani Regent has made variousresponsive efforts in the context of rebuilding public trust (trust building).However, the trust building effort still leaves important records that need to beunderlined. Trust building efforts undertaken by the Klaten Regency Governmenttend to prioritize the political interests of the Regent of Sri Mulyani in the lead-upto the 2020 elections rather than the aspects of bureaucratic reform. The KlatenRegency Government needs to rebalance the implementation of trust buildingefforts by emphasizing more on aspects of bureaucratic reform and setting asidethe incumbent's electoral political interests.Keywords: Public Trust, Trust Building, Bureaucratic Reforms, Political Interest